Trends in Youth Participation and Leadership in Indonesia: Analysis of Youth Development Index data 2015-2023 - Muhammad Syah Fibrika Ramadhan; Wiwin Rosmawati (Kirana Publisher (KNPub), 2026)
This study analyzes youth participation and leadership trends in Indonesia (2015–2023) using Youth Development Index (IPP) data from the Ministry of Youth and Sports. A quantitative, descriptive-analytical time-series approach was applied across 34 provinces. The results show youth social participation stabilized at 81.36% (2015–2020) but dropped significantly to 70.49% (2021–2022) due to the COVID-19 pandemic, before recovering to 71.44% in 2023. Conversely, organizational activity and meeting attendance remained stable. Striking regional disparities emerged: West Nusa Tenggara recorded the highest rate (87.31%), while DKI Jakarta recorded the lowest (38.3%). Overall, the Participation and Leadership Indicator Index stagnated at 46.67% and fell to 43.33%, reflecting suboptimal performance. The study concludes that youth development requires differentiated policy strategies based on regional characteristics, strengthening organizational ecosystems, leveraging digital transformation, and further research for effective policy interventions.